2017
DOI: 10.1007/s10488-017-0840-z
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Behavior Treatment Progress as a Function of Therapy Focus and Youth Diagnosis in a Community Mental Health Setting

Abstract: Monthly disruptive behavior treatment progress for 613 youth ages 7-18 receiving intensive in-home services was examined. Multilevel modeling indicated carrying a depressive mood diagnosis predicted less disruptive behavior progress compared to youth with only externalizing diagnoses. Paradoxically, more monthly focus on disruptive behavior treatment targets predicted lower concurrent progress ratings, while greater focus on depressive mood targets predicted greater disruptive behavior progress for youth with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…However, prior work has found these therapist reports to be reliable and valid. The reliance on a single-item outcome is a weakness, although present findings are consistent with patterns of treatment change (i.e., significant linear and quadratic time effects) typically observed during community care (e.g., Wilkie et al, 2018). In addition, studies such as these allow for an examination of treatment within complex public mental health community care, which often has cases with high levels of comorbidity and multiple targets of treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, prior work has found these therapist reports to be reliable and valid. The reliance on a single-item outcome is a weakness, although present findings are consistent with patterns of treatment change (i.e., significant linear and quadratic time effects) typically observed during community care (e.g., Wilkie et al, 2018). In addition, studies such as these allow for an examination of treatment within complex public mental health community care, which often has cases with high levels of comorbidity and multiple targets of treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Despite a large amount of variance occurring on the therapist level, this study found that none of the available therapist variables were significant predictors of improvement. Previous research examining these therapist variables (i.e., professional specialty, degree, licensure status) found similar nonsignificant predictors in the context of significant variance at this level of the model (Izmirian et al, 2019;Wilkie et al, 2018). Other therapist variables might be related to substance use treatment progress, such as theoretical orientation, prior training in and fidelity of evidencebased practices, and the ability to develop an effective therapeutic alliance.…”
Section: Hee and Muellermentioning
confidence: 77%
“…al's study also confirmed that mental health is likely to change on a monthly basis. 29,30 Given that other scholars have conducted causal inferences about mental health and other related variables based on the 2-wave method to varying degrees, this paper employed the 2-wave method to process data. 31,32 Provided that the data was collected through self-reported questionnaire, we adopted confirmatory factor analysis (CFA) to test the possible influences of CMV, using R (Version 3.5.3) and Lavaan Package (Version 0.6-3).…”
Section: Analyses Methodsmentioning
confidence: 99%
“…To date, students have authored or coauthored 52 peerreviewed publications and more than 119 professional conference presentations. Topics that have gone on to publication have varied from psychometric evaluations of system measures (e.g., Borntrager et al, 2013;Laba et al, 2022;Mah et al, 2019), predicting client outcomes (e.g., Holmes & Mueller, 2022;Milette-Winfree et al, 2017;Turner et al, 2022;Wilkie et al, 2018), and improving dissemination and implementation efforts (Chang et al, 2019;Izmirian et al, 2016;McLennan et al, 2019). In addition, RET has supported 23 theses and dissertations to date, some by clinical practicum students and some by other clinical psychology students who were mentored in the use of CAMHD data to answer specific research questions (RET, 2022).…”
Section: Research and Evaluation Training Student Trainingmentioning
confidence: 99%